Development of RME-Based LKPD Teaching Materials to Improve Students’ Learning Outcomes - Amianah, Siti; Masrifatin, Yuni (PGMI, STAI Miftahul Ula Nganjuk, 2024)
The development of teaching materials was carried out to facilitate students in understanding and completing learning materials in mathematics. Based on the results of interviews with the fourth-grade homeroom teacher at MI Al-Aziz, it was found that several students had mathematics learning outcomes below the Minimum Mastery Criteria (KKM), particularly in fraction topics. This condition was caused by the limited availability of teaching materials that were not able to attract students’ enthusiasm for learning. To address this problem, the researcher considered it necessary to develop teaching materials in the form of Student Worksheets (LKPD) based on Realistic Mathematics Education (RME). The research problems of this study are: (1) how to develop teaching materials based on Realistic Mathematics Education on fraction topics for fourth-grade students at MI Al-Aziz, and (2) how effective RME-based LKPD is in improving the learning outcomes of fourth-grade students at MI Al-Aziz. The objectives of this study are to develop RME-based teaching materials on fraction topics for fourth-grade students at MI Al-Aziz and to determine the effectiveness of RME-based LKPD on the learning outcomes of fourth-grade students at MI Al-Aziz. This research employed both qualitative and quantitative approaches. The type of research used was Research and Development (R&D), referring to the ADDIE model, which was adapted into five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The results of the study indicated that the developed teaching materials met the criteria of being very good, highly feasible, and valid, based on assessments by subject matter experts and design/media experts, with scores of 97.7% from material experts, 94.5% from design/media experts, and 88.3% from student assessments. Furthermore, the effectiveness results obtained from pretest and posttest instruments administered to students met the effectiveness criteria and were categorized as effective in improving the learning outcomes of fourth-grade students, with a percentage of 79%.